A phase-change thin film-tuned photonic crystal device. (23rd November 2018) - Liu, Longju; Mahmood, Russell; Wei, Le; Hillier, Andrew C; Lu, Meng
Abstract: This paper reports a tunable photonic device that incorporates a thin layer of phase-change material, Ge2 Sb2 Te5 (GST), in a photonic crystal (PC) structure. The PC structure is based on a one-dimensional grating waveguide with a metal cladding. The metal-cladded PC structure supports a guided-mode resonance (GMR) that selectively absorbs light at a particular wavelength. Inserting the GST material into the gating waveguide makes it possible to control the GMR mode. Here, the GST-PC device was numerically designed and optimized to obtain significant tuning of the GMR mode around 1550 nm. The tuning phenomena were experimentally demonstrated by the heat-induced phase change between crystalline and amorphous phases of the GST thin film. A spectral shift of the resonant wavelength from 1440 to 1610 nm was achieved via the crystallization process. The phase tuning of GST exhibits good repeatability as demonstrated by switching between amorphous and crystalline phases of GST for multiple cycles. The GST-PC device represents a new approach for tuning optical resonances with potential applications including but not limited to integrated photonic circuits, optical communications, and high-performance optical filters.